2014
DOI: 10.1177/0731684414565225
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermo-oxidative aging on the impact property of conventional and graphene-based carbon fabric composites

Abstract: The effects of reinforced structure (three-dimensional braided preform and laminated plain woven fabric) and graphene nanoplatelet-reinforced hierarchical interface on the impact properties of carbon fabric composites after thermo-oxidative aging were investigated. The results indicated that the impact properties decreased with increasing aging time due to the degradation of the matrix and fiber-matrix interface. After exposure to 140 C for 1200 h, the peak impact force and impact strength retention rates of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Tsotsis [2][3][4][5] found that the weight loss during thermo-gravimetric test could not be used as criteria for material acceptance. The properties' changes, such as mechanical properties [6][7][8][9][10][11][12], physical properties [13], thermal conductivity [14] and the development of microcracks [15][16][17] caused by thermal treatment have been extensively studied and documented. Compared with isothermal ageing, thermal cycling can accelerate the damage processes and especially the matrix crack propagation from the surfaces to the core of the laminate [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tsotsis [2][3][4][5] found that the weight loss during thermo-gravimetric test could not be used as criteria for material acceptance. The properties' changes, such as mechanical properties [6][7][8][9][10][11][12], physical properties [13], thermal conductivity [14] and the development of microcracks [15][16][17] caused by thermal treatment have been extensively studied and documented. Compared with isothermal ageing, thermal cycling can accelerate the damage processes and especially the matrix crack propagation from the surfaces to the core of the laminate [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have conducted study on the internal configuration and relative cross section assumption (Fang, et al 2009;Li, et al 2010), the elastic properties and strengths prediction and failure analysis of the braided composites. Different experimental, analytical, and numerical methods were employed (Ge et al 2018;Li et al 2014;Zhang et al 2015;Fan et al 2015;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions oxidation reaction/diffusion phenomena take place within the CFRPs and result in the deterioration of the matrix (such as weight loss, embrittlement, and chain scissions) and the fiber/matrix interfaces. 2–6 The thermo-oxidative degradation occurs initially at the outer surface of the composite and proceeds inwards via a diffusion mechanism. 7–10 Simultaneously, micro-cracks may occur due to the mismatches in the coefficients of thermal expansion between the fibers and matrix, as well as the resin shrinkage 11 caused by thermo-oxidative aging (TOA).…”
Section: Introductionmentioning
confidence: 99%